(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
The study was aimed at determining the effect of fertilizer element calcium and Bradyrhizobium inoculation in improving the yield and quality of groundnut seed. The experiment was conducted in 1997-78 and 1998-99 in the clay loam soil. The fertilizing element calcium significantly affected all the yield attributes and quality up to 150kg/ha and then decline. There was also an increasing trend in qualitative characteristics like percentage of oil and protein content of groundnut with the increase in the level of calcium from 0-150 kg/ha. Bradyrhizobium fertilization affected the yield significantly but most of the yield attributes was not affected significantly. Bangladesh J. Sci. Ind. Res. 41(3-4), 181-188, 2006